The outbreak of COVID-19 coronavirus and its impact on global mental health - Torales, Julio; O’Higgins, Marcelo; Castaldelli-Maia, João Mauricio; Ventriglio, Antonio (International journal of social psychiatry, 2020)
Background: The current outbreak of COVID-19 coronavirus infection among humans in Wuhan (China) and its spreading around the globe is heavily impacting on the global health and mental health. Despite all resources employed to counteract the spreading of the virus, additional global strategies are needed to handle the related mental health issues. Methods: Published articles concerning mental health related to the COVID-19 outbreak and other previous global infections have been considered and reviewed. Comments: This outbreak is leading to additional health problems such as stress, anxiety, depressive symptoms, insomnia, denial, anger and fear globally. Collective concerns influence daily behaviors, economy, prevention strategies and decision-making from policy makers, health organizations and medical centers, which can weaken strategies of COVID-19 control and lead to more morbidity and mental health needs at global level.